A narrative review of a low glycemic index dietary intervention during and after gestational diabetes mellitus - Mohamed Khir, Hannah Izzati; Mohd Yusof, Barakatun Nisak; Hasbullah, Farah Yasmin (Human Resource Management Academic Research Society, 2021)
Gestational diabetes mellitus (GDM) causes short- and long-term adverse health consequences, including postnatal DM among women post-GDM. This review synthesised the recent evidence about low glycemic index (GI) dietary intervention during and after GDM. Literature searches were conducted for articles published in English through two electronic databases, MEDLINE (for PubMed) and Science Direct, for studies that investigated the effects of a low GI during and after GDM. Eight studies met the criteria. Six studies were conducted among women with GDM during pregnancy, and two studies in women post GDM. In women with GDM, all studies had an intervention with a control group. Five studies reported at least one positive outcome in glucose levels, obstetric and fetal outcomes, or dietary intake compared to the control group. In women post GDM, one study had an intervention with a different control group, while another study was conducted within the same group but with a washout interval. Both studies reported at least one positive outcome in glucose levels, insulin sensitivity, or body weight reduction. The low GI diet intervention featured strategies to avoid and eliminate moderate to high GI foods and substitute high GI with low GI foods. The use of low GI diets during and after GDM provides some favourable outcomes. Further studies on diet GI in women post GDM are warranted to improve the quality of evidence tailored to a specific population.